Engineering Peroxidase Activity in Myoglobin: the Haem Cavity Structure and Peroxide Activation in the T67R/S92D Mutant and its Derivativere Constituted with Protohaemin-L-Histidine - RONCONE, RAFFAELLA; MONZANI, ENRICO; M. Murtas; BATTAINI, GIUSEPPE; SANANGELANTONI, ANNA MARIA; S. Zuccotti; BOLOGNESI, MARTINO; CASELLA, LUIGI (Biochemical Journal, 2004)
Protein engineering and cofactor replacement have been employed as tools to introduce/modulate peroxidase activity in sperm whale Mb (myoglobin). Based on the rationale that haem peroxidase active sites are characterized by specific charged residues, the Mb haem crevice has been modified to host a haemdistal Arg residue and a proximal Asp, yielding the T67R/S92D Mb mutant. To code extra conformational mobility around the haem, and to increase the peroxidase catalytic efficiency, the T67R/S92D Mb mutant has been subsequently reconstituted with protohaem-L-histidine methyl ester, yielding a stable derivative, T67R/S92D Mb-H. The crystal structure of T67R/S92D cyanometMb (1.4 Å resolution; R factor, 0.12) highlights a regular haem-cyanide binding mode, and the role for themutated residues in affecting the haem propionates as well as the neighbouring water structure. The conformational disorder of the haem propionate- 7 is evidenced by the NMR spectrum of the mutant. Ligandbinding studies show that the iron(III) centres of T67R/S92D Mb, and especially of T67R/S92D Mb-H, exhibit higher affinity for azide and imidazole than wild-type Mb. In addition, both protein derivatives react faster than wild-type Mb with hydrogen peroxide, showing higher peroxidase-like activity towards phenolic substrates. The catalytic efficiency of T67R/S92D Mb-H in these reactions is the highest so far reported for Mb derivatives. A model for the protein–substrate interaction is deduced based on the crystal structure and on the NMR spectra of protein–phenol complexes.